PENGARUH RETURN ON ASSET, BETA, DIVIDEND PAYOUT RATIO DAN TOTAL ASSET TURN OVER TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2020 - Dwi Putri Wilujeng; Budi Santoso; Burhanudin Burhanudin (Master of Management, Mataram University, 2023)
The purpose of this study is to examine the effect of Return On Asset, Beta, Dividend Payout Ratio and Total Asset Turn Over on the value of companies listed on the Indonesia Stock Exchange for the 2015-2020 period. This research is a quantitative research that is associative. Sampling is carried out using purposive sampling techniques. This study used a sample of 28 companies from 195 manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2020 period, so that the total observation in this research material was multiple linear regression analysis using Eviews version 12. The results of this study show that return on assets has a positive but not significant effect and total asset turn over has a negative but not significant effect on the value of the company. While beta and dividend payout ratio show a positive and significant influence on the value of the company. For further research, researchers are expected to expand the research object of Indonesian stock market business midwives so that they can add more diverse research variables.